Factors contributing to diurnal variation in athletic performance and methods to reduce within-day performance variation: A systematic review - Kusumoto. H.; Ta, C.; Brown, S. M.; Mulcahey, M. K. (The Journal of Strength and Conditioning Research, 2021)
For many individuals, athletic performance (e.g., cycle ergometer output) differs based on the time of day (TOD). This study identified factors contributing to diurnal variation in athletic performance and methods to reduce TOD performance variation. Comprehensive searches of PubMed, Ovid, EMBASE, Web of Science, and Cochrane Libraries were conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Peer-reviewed publications reporting quantitative, significant diurnal variation (p = 0.05) of athletic performance with explanations for the differences were included. Studies providing effective methods to reduce diurnal variation were also included. Literature reviews, studies involving nonhuman or nonadult subjects, studies that intentionally manipulated sleep duration or quality, and studies deemed to be of poor methodological quality using NIH Quality Assessment Tools were excluded. Forty-nine studies met the inclusion criteria. Body temperature differences (n = 13), electromyographic parameters (n = 10), serum biomarker fluctuations (n = 5), athlete chronotypes (n = 4), and differential oxygen kinetics (n = 3) were investigated as significant determinants of diurnal variation in sports performance. Successful techniques for reducing diurnal athletic performance variability included active or passive warm-up (n = 9), caffeine ingestion (n = 2), and training-testing TOD synchrony (n = 3). Body temperature was the most important contributor to diurnal variation in athletic performance. In addition, extended morning warm-up was the most effective way to reduce performance variation. Recognizing contributors to diurnal variation in athletic performance may facilitate the development of more effective training regimens that allow athletes to achieve consistent performances regardless of TOD.